Input files for simulations in: Lili Zhang, Zesheng Zhang, Mehrdad Negahban, Antoine Jérusalem, Molecular dynamics simulation of cell membrane pore sealing, Extreme Mechanics Letters, 2019, https://doi.org/10.1016/j.eml.2019.01.008. - Zhang, L (University of Oxford, 2019)
Cite reference: